Production and Fate of Methylated Sulfur Compounds from Methionine and Dimethylsulfoniopropionate in Anoxic Salt Marsh Sediments - Kiene, Ronald P. (1987)
Anoxic salt marsh sediments were amended with dl-methionine and dimethylsulfoniopropionate (DMSP). Microbial metabolism of methionine yielded methane thiol (MSH) as the major volatile organosulfur product, with the formation of lesser amounts of dimethylsulfide (DMS). Biological transformation of DMSP resulted in the rapid release of DMS and only small amounts of MSH. Experiments with microbial inhibitors indicated that production of MSH from methionine was carried out by procaryotic organisms, probably sulfate-reducing bacteria. Methane-producing bacteria did not metabolize methionine. The involvement of specific groups of organisms in DMSP hydrolysis could not be determined with the inhibitors used, because DMSP was hydrolyzed in all samples except those which were autoclaved. Unamended sediment slurries, prepared from Spartina alterniflora sediments, contained significant (1 to 10 μM) concentrations of DMS. Endogenous methylated sulfur compounds and those produced from added methionine and DMSP were consumed by sediment microbes. Both sulfate-reducing and methane-producing bacteria were involved in DMS and MSH consumption. Methanogenesis was stimulated by the volatile organosulfur compounds released from methionine and DMSP. However, apparent competition for these compounds exists between methanogens and sulfate reducers. At low (1 μM) concentrations of methionine, the terminal S-methyl group was metabolized almost exclusively to CO(2) and only small amounts of CH(4). At higher (>100 μM) concentrations of methionine, the proportion of the methyl-sulfur group converted to CH(4) increased. The results of this study demonstrate that methionine and DMSP are potential precursors of methylated sulfur compounds in anoxic sediments and that the microbial community is capable of metabolizing volatile methylated sulfur compounds.